Investigation of polarization state of terahertz radiation from compact laser-induced plasma in air. Issue 3 (4th February 2017) - Yousef-Zamanian, Abolfazl; Neshat, Mohammad
Abstract : A comprehensive theoretical study is presented on the polarization state of THz wave radiation from a two-colour laser-induced plasma, and its dependency on optical pulse polarizations and phase difference. We extend the so-called photocurrent model to calculate three-dimensional distribution of photocurrent from which the polarization state of the THz radiation is calculated. It is shown that the calculation results from the photocurrent model, is in agreement with the previously reported experiments. Moreover, we show the possibility of creating any desired polarization state (i.e. elliptical, circular or linear) for the THz radiation through such generation mechanism by adjusting proper parameters.